Pengaruh Terpaan Iklan Televisi dan Intensitas Word of Mouth terhadap Keputusan Pembelian di Shopee - Rahmasari Tunggal Sukma, Dinda; Yulianto, Muchammad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This study aims to determine the effect of exposure to television advertising and the intensity of word of mouth communication on purchasing decisions at Shopee. In determining the hypothesis, this study uses the theory of Advertising Exposure and the Traditional Word Of Mouth Communication Theory. To determine the sample, this study uses non-probability sampling techniques with the type of purposive sampling. The research sample consisted of 60 people with the characteristics of residents who live in Semarang with the age of 21-49 years and exposed to Shopee ads on television and do word of mouth communication related to Shopee. Analysis of the data used in this study is Simple Linear Regression Analysis. Based on the results of the analysis note that there is an influence between the exposure to television advertising on purchasing decisions in Shopee by 46% with a significant correlation between the two variables. The effect of the intensity of word of mouth communication on purchasing decisions in Shopee was 56.4% with a significant correlation between the two variables. The purchase decision at Shopee is relatively high with a percentage of 77% deciding to make a purchase at Shopee.